Hepatoprotective Effect of Vitamin C and E on Antitubercular Drugs Induced Hepatotoxicity in Albino Rats - Babul Kumari (Journal of Global Pharma Technology, 2018)
Objective- The hepatoprotective effects of Vitamin C and E were investigated in anti tubercular drugs induced hepatotoxicity in albino rats. Methods- Liver necrosis was induced by a combination of three anti tubercular drugs [isoniazid (I) 7.5mg/kg, Rifampin (R) 10 mg/kg and Pyrazinamide (P) 35mg/kg] given orally as a suspension for 30 days in rats. The liver damage was evidenced by the histological architectures of the liver tissues and the elevated levels of the liver enzymes like SGOT, SGPT, ALP, Total bilirubin, and unconjugated bilirubin. Results- Treatment with Vitamin C (250 mg/kg) and E (250 mg/kg,) significantly (P<0.05-P<0.001)  reduces the anti tubercular drugs induced elevations of the liver enzymes like SGOT, SGPT, ALP, Total bilirubin, and unconjugated bilirubin. Histological architectures of the liver tissues become normal in vitamin -treated group a comparison to the hepatotoxic group. Conclusion-The results of this study suggest that Vitamin C and E have a hepatoprotective effect against anti tubercular drugs induced hepatotoxicity in albino rats.Keywords:  Vitamin C, Vitamin E, Isoniazid, Rifampicin, Pyrazinamide, liver enzymes.